A case of an Aberrant branch from the posterior brachial cutaneous nerve to the latissimus dorsi: a vestigeal part of the dorsoepitrochlearis? - Aung, Htar Htar; Sakamoto, Hirokazu; Akita, Keiichi; Sato, Tatsuo (Okajima Foria Anatomica Yaponika Henshubu, 2000)
Summary: During dissection, an aberrant muscular nerve to the small part of the latissimus dorsi arising from the posterior brachial cutaneous nerve was found. Based on the findings of the form and the innervations, the small part is considered to be a vestige of the dorsoepitrochlearis in mammals. It is suggested that the posterior brachial cutaneous nerve is derived from the nerve to the dorsoepitrochlearis (Kasai et al., 1989, Acta Anat Nippon 64:255-266). This case may be indirect evidence indicating one of the patterns of development of cutaneous nerves in man.